2022
DOI: 10.3390/diabetology3040049
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Free and Added Sugars and Their Nutritional Impact in Diabetic Patients

Abstract: A high consumption of sugar leads to an increase in caloric intake, which in turn will lead to a higher risk of developing health issues. Foods contain both naturally occurring sugars and added sugars. The World Health Organization recommends that the daily intake of free sugars be below 10% of the total daily energy intake. Food performs a key role in maintaining an adequate glycaemic control in people with diabetes. However, there is a low compliance to dietary recommendations, namely in the amount of sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Although in some studies, the healthy pattern or the Mediterranean pattern or DASH, which are types of healthy patterns, due to their high fiber content, phytoestrogen, minerals, soy content, and as a result high isoflavones reduce low-density lipoprotein (LDL) and increase HDL (Azadbakht et al , 2007; Jenkins et al , 2002), so decrease the incidence of MetS (Hassannejad et al , 2018; Esmaillzadeh et al , 2007; Asghari et al , 2016; Godos et al , 2017; Salas-Salvadó et al , 2015; Hershey et al , 2021), but some studies have not observed this relationship, including a case-control study whose healthy pattern is similar to our healthy pattern containing fruit, dried fruit, fruit juice and vegetables and dairy products (Kelishadi et al , 2018). The reason for contrast and not observing the relationship in our study is that fruit juice, sweets and desserts consumption was high in this pattern (Faith et al , 2006), which leads to abdominal obesity and increases blood sugar, and as a result, affects MetS (Riseberg et al , 2021; Fernandes et al , 2022).…”
Section: Discussioncontrasting
confidence: 68%
“…Although in some studies, the healthy pattern or the Mediterranean pattern or DASH, which are types of healthy patterns, due to their high fiber content, phytoestrogen, minerals, soy content, and as a result high isoflavones reduce low-density lipoprotein (LDL) and increase HDL (Azadbakht et al , 2007; Jenkins et al , 2002), so decrease the incidence of MetS (Hassannejad et al , 2018; Esmaillzadeh et al , 2007; Asghari et al , 2016; Godos et al , 2017; Salas-Salvadó et al , 2015; Hershey et al , 2021), but some studies have not observed this relationship, including a case-control study whose healthy pattern is similar to our healthy pattern containing fruit, dried fruit, fruit juice and vegetables and dairy products (Kelishadi et al , 2018). The reason for contrast and not observing the relationship in our study is that fruit juice, sweets and desserts consumption was high in this pattern (Faith et al , 2006), which leads to abdominal obesity and increases blood sugar, and as a result, affects MetS (Riseberg et al , 2021; Fernandes et al , 2022).…”
Section: Discussioncontrasting
confidence: 68%
“…Furthermore, people's preferences in reading nutritional facts and other important details about food products affect UPF intake. Mostly, they prioritize taste and price over noting ingredients (including caloric values and other listed ingredients) [44].…”
Section: Hazard Ratio Associated With Consuming Upfs and Developing Ncdsmentioning
confidence: 99%